Phase transition, thermal stability, and molecular dynamics of organic–inorganic hybrid perovskite [NH3(CH2)6NH3]CuCl4 crystals. Issue 32 (20th July 2022) - Choi, Moon Young; Lee, Seon Ju; Ju, Huiyeong; Lim, Ae Ran
Abstract : Powder X-ray diffraction patterns of [NH3 (CH2 )6 NH3 ]CuCl4 at different temperatures. Abstract : Organic–inorganic hybrid perovskites have various potential applications in fuel cells and solar cells. In this regard, the physicochemical properties of an organic–inorganic [NH3 (CH2 )6 NH3 ]CuCl4 crystal was conducted. The crystals had a monoclinic structure with space group P 21 / n and lattice constants a = 7.2224 Å, b = 7.6112 Å, c = 23.3315 Å, β = 91.930°, and Z = 4 at 300 K, and the phase transition temperature ( T C ) was determined to be 363 K by X-ray diffraction and differential scanning calorimetry experiments. From the nuclear magnetic resonance experimental results, the changes in the 1 H chemical shifts in NH3 and the influence of C1 located close to NH3 in the [NH3 (CH2 )6 NH3 ] cation near T C are determined to be large, which implies that the structural change of CuCl4 linked to N–H⋯Cl is large. The 1 H spin–lattice relaxation time ( T 1ρ ) in NH3 is shorter than that of CH2, and the 13 C T 1ρ values for C1 close to NH3 are shorter than those of C2 and C3 due to the influence of the paramagnetic Cu 2+ ion in square planar geometry CuCl4 . The structural mechanism for the phase transition was the change in the N–H⋯Cl hydrogen bond and was associated with the structural dynamics of the CuCl4 anion.